A team approach to reducing Clostridium difficile and MRSA bacteraemias - Roberts, Sue (International Journal of Infection Control, 2008)
The infection control and prevention team at East Kent Hospitals NHS Trust decreased the number of healthcare-associated infections considerably following the introduction of a range of methods and interventions. The hospital saw a 49% reduction in cases, with no cases of bacteraemias found in January 2008. Clostridium difficile rates per 1,000 bed days between April 2007 and January 2008 were 0.82 per 1,000 bed days – one of the lowest rates in the NHS. The introduction of root cause analysis in 2007 for all C. difficile cases assisted in the decline in infection numbers.